(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2018)
The study explores the situations surrounding the relationship between Western Television Programmes and the cultural values of the Nigerian youth population, with particular reference to Taraba State University where constructive generalizations were made. Findings were backed-up with an empirical research on 145 respondents from the study area. Cross-sectional Survey design was adopted for this work. The bottle spinning sample technique was used alongside availability/convenient sampling technique. The study also made used of questionnaire as a means of quantitative data collection. The SPSS (Statistical Packages for Social Sciences) was employed for data analysis and subsequently justified using manual procedures. Six (6) research questions were utilized in empirically justifying the work. Finally, the study discovered that Nigerian Youth prefer viewing WTP more to indigenous TV programmes and this exerts great influence on their cultural values. The study recommends that in salvaging the undue influence vented on the cultural values of youth by Western Television Programmes, there is the need for a constant review of the schooling content of the Nigerian education system, such that its culture would be lucidly pronounced.